A Review: Adsorption and Removal of Heavy Metals Based on Polyamide-amines Composites - Wang, Qian; Zhu, Sining; Xi, Chen; Zhang, Fan (Frontiers in Chemistry, 2022)
In recent years, how to develop new heavy metal adsorption materials has become research hot pot because of the problem of heavy metal pollution. Polyamide-amines (PAMAMs) have strong attention from the researchers due to their advantages of macro-molecular cavity, dense surface functional groups, non-toxic, efficient and easy modification. Therefore, the development of polymer composites based on PAMAMs has increasingly become an important research direction to solve heavy metal pollution. In this paper, the preparation of the composites based on PAMAMs and inorganic functional component or organic functional groups and its application on the adsorption of heavy metals were reviewed. Meanwhile, their subsequent applications and shortcomings are prospected.